1991
DOI: 10.1073/pnas.88.10.4148
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipopolysaccharide stimulates protein tyrosine phosphorylation in macrophages.

Abstract: Lipopolysaccharide (LPS), a membrane component of Gram-negative bacteria, stimulates immune responses by activating macrophages, B lymphocytes, and other cells of the immune system. The mechanisms by which LPS activates these cells are poorly characterized. Since protein tyrosine phosphorylation appears to be a major intracellular signaling event that mediates cellular responses, we examined whether LPS alters tyrosine phosphorylation in macrophages.We found that Escherichia coli K235 LPS increased tyrosine ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
213
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(220 citation statements)
references
References 32 publications
6
213
1
Order By: Relevance
“…The increases in MAPK activity observed in the in vitro kinase assay were consistent with observation of decreased migration of immunoreactive MAPK. This result is indicative of increased tyrosine phosphorylation, which has been shown to correlate with increased MAPK activity (51,74). These results demonstrate that LPS treatment as well as transfection with pRSV-Raf-BXB increases p42 MAPK activity in RAW 264.7 cells.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The increases in MAPK activity observed in the in vitro kinase assay were consistent with observation of decreased migration of immunoreactive MAPK. This result is indicative of increased tyrosine phosphorylation, which has been shown to correlate with increased MAPK activity (51,74). These results demonstrate that LPS treatment as well as transfection with pRSV-Raf-BXB increases p42 MAPK activity in RAW 264.7 cells.…”
Section: Resultssupporting
confidence: 61%
“…LPS is thought to signal in part through interaction with CD14, a glycosylphosphatidylinositol-linked protein found on the surface of monocytic cells (76). Signaling events which have been identified in monocytic cells following stimulation with LPS include phosphorylation of a number of cellular proteins and activation of the Src family tyrosine kinases Lyn, Hck, and Fgr (68,74,75). In addition, LPS stimulation has been reported to activate p42/44 mitogenactivated protein kinases (MAPKs) in monocytes and macrophages (44,75).…”
mentioning
confidence: 99%
“…We also found Syk expression in human nasal polyp-derived fibroblasts. LPS augments tyrosine phosphorylation (11,12,14), which results in phosphorylation or activation of mitogen-activated protein (MAP) kinases: 44-and 42-kDa MAP kinases (extracellular signal-related kinase 1 and 2) (14, 32), stress-activated protein kinase/ JNK (33), and p38 kinase (10,14,34). In this study, we demonstrated that LPS induced tyrosine phosphorylation of Syk and activated JNK1 in nasal fibroblast lines.…”
Section: Discussionmentioning
confidence: 80%
“…LPS has been reported to increase tyrosine phosphorylation in macrophages [21,22,31]. Since little is reported about the effects of pathogens other than LPS, it is of interest to examine whether the phosphorylation is an event commonly induced by diverse TLR ligands or an event specifically induced by LPS.…”
Section: Pathogen-induced Protein Tyrosine Phosphorylation and Its Inmentioning
confidence: 99%